Pengembangan Profesionalisme Guru dalam Pembelajaran Bahasa Indonesia Pada Kurikulum Merdeka (International Forum of Researchers and Lecturers, 2024)
The purpose of this article is to determine the development of teacher professionalism in curriculum-based independent learning. The method used in this research is qualitative. Data was collected through observation and interviews with teachers. The independent curriculum implemented in various schools emphasizes subjects, including Indonesian. The support of professional organizations really supports teachers in their academic preparation to carry out independent learning. Teachers are trained in independent curriculum learning, the core of the independent curriculum, especially the Independent Curriculum, is present to complement the implementation of the Curriculum. The implementation of independent learning programs in various schools allows teachers to catch up in reading, writing and arithmetic. For students, an independent program can provide a solution to complete the program, before the program can be implemented in stages depending on the level of readiness of each school.